The demographic collapse of hunting in the Iberian Peninsula - Mario Gaspar; Pelayo Acevedo; Eneko Arrondo; Ignacio García‐Martínez; Juan Herrero; Roberto Pascual‐Rico; José A. Sánchez‐Zapata; José D. Anadón (People and Nature)
Abstract Hunting is one of the oldest and most relevant extractive activities performed by humans in nature. Over the last century hunting has experienced profound changes in developed countries, shifting from a consumption to a recreational activity and declining in some countries. However, substantial quantitative information on these trends at large temporal scales, as well as the projection of the number of hunters and their demographic structure under future scenarios is lacking at regional scales. Here we (i) describe the current demography of hunters in a large portion of the Iberian Peninsula, (ii) quantify population and recruitment trends for the last five decades and (iii) starting from those trends, we project the number and structure of hunters for the following decades. At present, the studied hunting population, with nearly 600,000 hunters, is strongly ageing, with the most abundant cohort being that between 61 and 70 years, and its prevalence is eight times higher on the smallest towns than in the large cities. Over the last 15 years hunters have declined by 26%, while over the last 50 years it has declined by 45%. This trend is linked to a steady decline of recruitment of young hunters that has been overall reduced by 89% in the last 50 years. By 2050, if following average trends observed during the last five decades, hunters in the whole study area are expected to decrease by 70%, and the proportion of hunters aged over 60 will increase from 40% to 61%. Overall, our results indicate an ongoing collapse of the population of hunters in the Iberian Peninsula due to lack of recruitment, which began at least five decades ago. This collapse, together with other post‐rural abandonment processes (e.g. livestock and wood‐collection) is likely having a deep impact on wildlife populations and ecosystems, which is largely understudied. In this new post‐abandonment state, approaches to environmental management should be adapted to accommodate these ongoing, long‐term socio‐ecological shifts. Read the free Plain Language Summary for this article on the Journal blog.